Analysis of the sidewall dynamics of a gully system: causes and processes - Stefanuto, Estêvão Botura [UNESP]; Lupinacci, Cenira Maria [UNESP] (Universidade Federal do Paraná, 2023)
Globally, gullies appear to be a complex phenomenon due to their multi-causal and non-coincidental conditions, with variations in their temporal and spatial dimensions. In this sense, the aim is to evaluate the evolutionary dynamics of the sidewall gullies system, aiming to understand its interaction with rainfall events, as well as the active dynamization mechanisms. For this, a gully system was selected with differentiated morphology, presenting a sidewall organized into two levels, located in the Paulista Peripheral Depression in the Corumbataí city, São Paulo. The sidewall was monitored from stakes installed around them over an 11 quarter period. In this way, it was verified that two evolutionary dynamics act on the sidewall, namely the loss of material associated with the undermined blocks, erosion by waterfalls and the action of the water channel, and the expansion of the material related to undermined blocks processes in progress, as well as the expansion of the materials by hydration and the occupation of the reading points by grasses. It was also found that the presence of cattle may have contributed to greater sidewall dynamics, since most of the monitoring periods, after the removal of the cattle, showed a reduction in the values of material loss. Finally, rainfall is also a variable of interest, with part of the analyzed quarters showing consonance between increased rainfall and increased material loss, and part showing an inverse relationship between rain and material loss, which may be associated to the little intense rains and the antecedent wetness.
Análise da dinâmica do talude erosivo de um sistema em voçorocamento: causas e processos
Keywords: Erosion monitoring; Gully erosion; Material loss and expansion; Rainfall intensity